Differentiating the barriers to adequate prenatal care in Missouri, 1987-88. - Sable, M R (1990)
Inadequate prenatal care has previously been identified as a significant risk factor for women who have low birth weight infants and infants who die during the neonatal period. Postpartum interviews with 1,484 primarily low-income women were conducted during 1987-88 in three areas of Missouri with the highest rates of inadequate prenatal care. The purpose of the study was to identify barriers to prenatal care and to determine which barriers differentiated between women receiving adequate and those receiving inadequate prenatal care. Women who received inadequate prenatal care were more likely to be black, unmarried, higher parity, and have less education than those who received adequate care. These women were also more likely to be poor, Medicaid-eligible, to have had an unwanted pregnancy, more stress and problems during pregnancy, and less social support. In the multivariate analysis, race and marital status lost their importance. The strongest predictor of inadequate prenatal care was women not knowing that they were pregnant in the first 4 months of pregnancy (adjusted odds ratio 9.28). To improve the rate of adequate prenatal care, society must address the issues of poverty and wantedness of pregnancy.